Ambiguity-generating devices in linguistic verbal jokes - Lew, Robert (My University, 2010)
The paper argues that ambiguity is a desirable and purposeful element of linguistic verbal jokes and explains and illustrates the mechanisms which support ambiguity.
Unpublished paper, written in 1996.
Keywords: ambiguity; jokes; humour; linguistic humour